Use of artificial intelligence in the internal audit of sustainable procurement - Kamal, Mustofa (Badan Pemeriksa Keuangan Republik Indonesia, 2025)
Internal auditors have not yet achieved optimal implementation of data analytics, and the limited progress of electronic-based government system audits has encouraged the use of big data analytics in internal auditing. This study aims to examine the application of artificial intelligence in sustainable public procurement audits for the development of Indonesia’s new capital. An exploratory case study was employed using spreadsheet-based analysis and OpenAI tools to process data from 23 construction projects in 2023 and 841 Village Development Index observations in East Kalimantan. ChatGPT was used to identify ten sustainability-related risks, prepare corresponding audit programs, determine ten development areas, and generate seven recommendations, and the resulting outputs were reviewed using human professional judgment. The findings reveal a major risk of a lack of transparency in procurement planning documents and highlight the need for greater collaboration among procurement authorities, local governments, and village communities. The study concludes that AI can serve as an audit support tool for risk identification and audit planning, while human judgment remains essential to ensure contextual accuracy. The results provide practical implications for strengthening sustainable procurement oversight in public infrastructure projects. The novelty of this study lies in demonstrating a spreadsheet-based workflow that integrates AI into internal audit procedures for sustainable procurement.